PERCEPTIONS OF TEACHERS ON THE USE OF HISTORY IN TEACHING MATHEMATICS - Author02 02 (SAMPURASUN, 2017)
Abstract In this study, we looked into the views of teachers on the use and the extent of their use of mathematics history in the classroom. A total of 72 teachers across the three levels-primary, secondary, and tertiary, from both public and private schools participated in the study. It was found out that there was no significant difference in the perceptions on the use of history of teachers across level but there was a significant difference in the perceptions of teachers depending on whether they came from a private or public school. In terms of the extent of use, teachers, regardless of the level and type of school in which they came from, sometimes use teaching methods which incorporate the history of mathematics. Keywords: History, Mathematics Education, Perceptions, Teaching Methods